Study guides

☆☆

Q: How do you you factor 4x squared minus 6x minus?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x2 - 6x - 27 = (x-9)(x+3)

3x(6x - 1)

(2x - 1)(6x + 5)

It is: (2x+3)(3x-8) when factored

It is: (3x+4)(2x-3) when factored

Related questions

(4x - 3)(2x + 3)

8x^2 + 6x - 5 = 8x^2 + 10x - 4x - 5 = 2x * (4x + 5) - (4x + 5) = (2x -1) * (4x + 5)

x2 - 6x - 27 = (x-9)(x+3)

3x(6x - 1)

(3x + 2)(2x - 3)

(2x - 1)(6x + 5)

(2x+5)(4x-7)

8x2 + 6x - 9 = 8x2 + 12x - 6x - 9 = 4x(2x + 3) - 3(2x + 3) = (2x + 3)(4x - 3)

The GCF for the numerical part is 2 . The factors for x2 are xâ‹…x x â‹… x . The factor for x1 is x itself

x^2-4x/x^2-6x+8 = x(x-4)/(x-2)(x-4) = x/(x-2)

It is: (2x+3)(3x-8) when factored

(6x - 1)(6x - 1)

People also asked